Green diesel production from palm fatty acid distillate over SBA-15-supported nickel, cobalt, and nickel/cobalt catalysts - Kamaruzaman, Muhammad Fadhli; Taufiq-Yap, Yun Hin; Derawi, Darfizzi (Elsevier, 2020)
The utilization of non-edible and low-cost feedstock in bioenergy research is getting more attention in recent decades. Catalytic deoxygenation of fatty acids from waste oil feedstocks is a promising route to produce diesel-like hydrocarbons. Here we report the conversion of palm fatty acid distillate (PFAD), a low-value side product of physical refining of crude palm oil, into green diesel using a solventless and hydrogen-free deoxygenation (DO) reaction using catalytic deoxygenation over solid acid catalysts (Co/SBA-15, Ni/SBA-15, and Ni–Co/SBA-15) with total metal loadings of 5 wt%. Metal precursors (Ni, Co, Ni–Co) were doped on the mesostructured catalyst supporter, SBA-15 by wet impregnation. The catalysts were characterized by nitrogen adsorption-desorption isotherm analysis, X-ray diffraction, X-ray fluorescence, infrared spectroscopy, and high-resolution transmission electron microscopy with elemental mapping. The DO reaction was carried out in a semi-batch reactor with a catalyst loading of 10 wt% at 350 °C for 3 h. The use of both Ni/SBA-15 and Ni–Co/SBA-15 afforded products with high contents of liquid hydrocarbons (C8–C17) with yields of 85.8% and 88.1%, respectively, and selectivity for diesel-range hydrocarbons (C13–C17) above 85% were achieved. Cobalt seems to have a larger particle size, then associates with the carbon formation and introduces coke formation. It blocks some pores and deactivates the active sites of the catalyst, thus reducing the catalytic activity.